The impact of letrozole administration on oocyte morphology in breast cancer patients undergoing fertility preservation - Bercaire, Ludmila M.N. [UNESP]; Cavagna, Mario; Donadio, Nilka F.; Rocha, Andressa R.; Portela, Rafael; Alves, Vanessa R.; Santos, Thamara B.B.; Cavagna, Felipe; Dzik, Artur; Gebrim, Luiz H.; Nahas, Eliana A.P. [UNESP] (GN1 Sistemas e Publicacoes, 2020)
Objective: Patients submitted to oncological fertility preservation with letrozole and gonadotropins seem to present a higher rate of immature oocytes and lower fertilization rates in comparison to infertile patients submitted to IVF cycles with gonadotropins. The aim of this study was to evaluate the influence of letrozole on oocyte morphology in patients with breast cancer submitted to fertility preservation. Methods: Retrospective analysis performed at a pub-lic tertiary hospital in São Paulo, Brazil. The oocytes were retrieved from patients with breast cancer undergoing fertility preservation (n=69), and from infertile women undergoing in vitro fertilization (n=92). We evaluated 750 oocytes obtained from breast cancer patients submitted to ovarian stimulation with letrozole and gonadotropins, and 699 oocytes from patients without breast cancer submitted to ovarian stimulation for in vitro fertilization with go-nadotropins only due to male factor infertility. The mature oocytes retrieved were analyzed for the presence of re-fractile bodies, ooplasm color and regularity, central granulation degree, cortical granules, zona pellucida staining and regularity, perivitelline space, presence of vacuoles or abnormal smooth-surfaced endoplasmic reticle and oocyte retraction. Results: There was a higher incidence of alterations in oocyte morphology in the letrozole group when com-pared to the control group: increased perivitelline space (p=0.007), irregular zona pellucida (p<0.001), refractile bodies (p<0.001), dark ooplasm (p<0.001), granular oo-plasm (p<0.001), irregular ooplasm (p<0.001) and dense central granulation (p<0.001). Conclusion: Letrozole is a risk factor for worse oocyte morphology. However, the clinical impact of ovarian stimulation protocol with combined use of gonadotropins and letrozole for fertility preservation remains unclear in this setting. These data underline the importance of establish-ing the predictive potential of morphological dimorphisms of human oocytes in IVF outcomes.
Keywords: Fertility preservation; In vitro fertilization; Oocyte morphology; Random-start ovarian stimulation